Systemic Lactate Acts as a Metabolic Buffer in Humans and Prevents Nutrient Overflow in the Postprandial Phase - Schlicker, Lisa; Zhao, Gang; Dudek, Christian-Alexander; Boers, Hanny M.; Meyer-Hermann, Michael; Jacobs, Doris M.; Hiller, Karsten (Frontiers in Nutrition, 2022)
On an organismal level, metabolism needs to react in a well orchestrated manner to metabolic challenges such as nutrient uptake. Key metabolic hubs in human blood are pyruvate and lactate, both of which are constantly interconverted by very fast exchange fluxes. The quantitative contribution of different food sources to these metabolite pools remains unclear. Here, we applied in vivo stable isotope labeling to determine postprandial metabolic fluxes in response to two carbohydrate sources of different complexity. Depending on the ingested carbohydrate source, glucose or wheat flour, the net direction of the lactate dehydrogenase and the alanine amino transferase fluxes were adjusted in a way to ensure sufficient availability, while, at the same time, preventing an overflow in the respective metabolite pools. The systemic lactate pool acts as a metabolic buffer which is fueled in the early- and depleted in the late- postprandial phase and thus plays a key role for systemic metabolic homeostasis.